A study to assess the effectiveness of the structured teaching program on knowledge regarding reproductive health among adolescent girls of a selected school, Kanyakumari District. - Sudheesh kumar, Krishnan Nair; Vasudevan, Jaishree; Subhala, Subhala (Journal of Neonatal Surgery, 2025)
N